Neuroprotective effects of Thalassia testudinum leaf extract BM-21 on focal ischemia in rats - Teidy E. García; Roberto Menéndez; Felicia Rivera; Anoland Garateix; Ruth A. Morales; Erik Regalado; Juan C. Rodríguez; Federico Dajas (GarVal Editorial Ltda., 2017)
Context: The extract from the marine plant Thalassia testudinum BM-21, standardized to thalassiolin B content (5.8 ± 0.3%), possesses antioxidant, anti-inflammatory and neuroprotective effects on acrylamide-induced neurotoxicity in mice and global ischemia in Mongolian gerbils. Aims: To determine whether or not BM-21 possesses neuroprotective effects against cerebral ischemia induced by permanent middle cerebral artery occlusion (pMCAo), a clinically relevant model of stroke. Methods: BM-21 was administered orally (400 mg/kg, once-a-day/10 days) prior to ischemia. Twenty-four hours after occlusion, we studied neurological signs, infarct volume, cerebral edema, histological damage and oxidative stress in cortex and striatum. In addition, brain susceptibility to in vitro lipid peroxidation induced by kainic acid and 2,2'-azobis(2-amidinopropane) dihydrochloride was studied after the BM-21 administration. Results: BM-21 prevented behavioral deficit; reduced infarct volume and cerebral edema; markedly decreased neuronal damage in striatum and cortex region. After occlusion, there was a significant increase of oxidative stress in cortex and striatum. Treatment of ischemic rats with BM-21 (400 mg/kg) prevented lipid peroxidation and protein damage and increased the antioxidant enzymatic activities and glutathione. BM-21 also inhibited the in vitro lipid peroxidation in total brain homogenates. Conclusions: Oral pre-treatment of BM-21 protects rats against pMCAo ischemia-induced damage in the striatum and cortex. Results suggest that the protection of BM-21 involve at least partially, the increase resistance to oxidative stress.